Building Blocks for Quantum Network Based on Group‐IV Split‐Vacancy Centers in Diamond. Issue 2 (15th October 2019) - Chen, Disheng; Zheludev, Nikolay; Gao, Wei‐bo
Abstract: One ultimate goal of quantum information processing is to construct a quantum network for direct sharing of quantum information between distant parties based on stationary qubits for information storage and flying qubits for information transmission. This requires long‐lived quantum memories, efficient light–matter interface, and deterministic quantum gate operations. Among matter qubits, the electron spin of nitrogen vacancy center in diamond is an appealing option for its long coherence time at room temperature, deterministic microwave control, and optical preparation and readout of the qubit. However, its poor optical properties, including weak zero‐phonon‐line emission and large spectral diffusion, limit its potential for large‐scale deployment in quantum nodes. This has motivated the investigation for alternative quantum emitters that combine long‐time memory and coherent optical properties together. The emerging group‐IV split‐vacancy color centers in diamond, such as silicon‐vacancy, germanium‐vacancy, tin‐vacancy, and lead‐vacancy centers, are promising candidates of this ongoing exploration. These quantum emitters simultaneously possess microsecond spin coherence time and optically bright transitions with narrow linewidths. This review reports recent efforts on extending the spin coherence time of these color centers via temperature, strain, and charge control, which paves the road towards constructing solid‐based matter–photon interface for quantum network applications. Abstract : This article provides a review of the recent progress on coherent control of quantum states in split‐vacancy color centers in diamond, and the efforts for extending the coherence time of qubits composed of spin states. Together with excellent optical properties and continuous development of diamond nanophotonics, these quantum emitters act as promising building blocks for solid‐based quantum networks.